2002
DOI: 10.1536/jhj.43.423
|View full text |Cite
|
Sign up to set email alerts
|

Left Circumflex Coronary Artery Bridging.

Abstract: SUMMARYMyocardial bridging most frequently occurs on the left anterior descending coronary artery and may cause ischemia and related complications. Right coronary artery myocardial bridges (MB) are rare. We report a patient with an unusual coronary bridge, a left circumflex coronary artery bridge, who presented with exercise-induced angina pectoris that was relieved with medical therapy. (Jpn Heart J 2002; 43: 423-427) Key words: Myocardial bridging, Left circumflex coronary artery, Ischemia, Betablocker th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 15 publications
0
11
0
1
Order By: Relevance
“…[2] reported that out of 61 patients with a myocardial bridge, only one had an additional myocardial bridge of the posterior descending branch of the right coronary artery. In the literature, there are few reported cases of a myocardial bridge in the left circumflex coronary artery [3]. One of these reported patients had myocardial infarction treated by stenting of the bridged segment [4].…”
Section: Discussionmentioning
confidence: 99%
“…[2] reported that out of 61 patients with a myocardial bridge, only one had an additional myocardial bridge of the posterior descending branch of the right coronary artery. In the literature, there are few reported cases of a myocardial bridge in the left circumflex coronary artery [3]. One of these reported patients had myocardial infarction treated by stenting of the bridged segment [4].…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial bridges are one of the non-atherosclerotic anatomical abnormalities of the coronary arteries (Okmen et al 2002) . It has been suggested that the number, extent and the location of the myocardial bridges may have clinical significance (Bezerra et al 1987).…”
Section: Discussionmentioning
confidence: 99%
“…The wide variation in frequency shows that many bridges do not produce symptoms during life and thus, the individuals with the bridges are not subjected to diagnostic arteriography (De Winter et al,1998). Moreover, arteriography is more likely to identify deep versus superficial bridging (Ferreira et al,1991; Okmen et al,2002). In association with other clinical conditions, the prevalence of myocardial bridges in children with hypertrophic cardiomyopathy has been found to be greater than in the general population and has been identified in up to 25% of these patients (Reig et al,1990; Yetman et al,1998; Gow,2002).…”
Section: Frequency and Structure Of Bridgesmentioning
confidence: 99%